Racial and ethnic discrimination: regulatory framework, forms and protection - Solanes Corella, Ángeles (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
In recent decades there has been a significant development of European and international legal instruments related to prohibiting racial and ethnic discrimination. Nevertheless, this regulatory framework needs further improvement and implementation so that it can also combat new forms of discrimination. Along these lines, this article critically reviews international and European laws on discrimination and sets out the current state of the question. Based on this analysis, it proposes strengthening legal standards to reinforce protective measures against discrimination and enhancing the role of specialised bodies to foster equality, with the end purpose of fighting against racial and ethnic discrimination more effectively and efficiently.
Keywords: racial and ethnic discrimination; anti-discrimination laws; forms of discrimination; ECHR and ECJ jurisprudence; equality bodies